Development of Learning Media Uses Geogebra Application with Basket ball Context on Square Function Material - Muhammad Renaldy Pratama; Rani Sugiarni; Ahmad Faizun (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
The research is aimed at developing mathematical learning media with the help of the GeoGebra Application with basket ball context on square function material that tests its validity and practicality. This research uses the development research method with ADDIE design, but developed in this research is the GeoGebra Application to square function Materials with basket ball context. Participants in to see this validation by 2 experts and 8 high school students in Cianjur district. Research procedures include analysis, design, development, implementation and evaluation. The instruments used are validation sheets and practicality. Based on the results of the research showed that the application of GeoGebra with basket ball context on the square function material of the validator results is good and validated and practical at the time students use it.